Mill on the primacy of practical reason. (28th May 2018) - Macleod, Christopher
Abstract: In this article, I explore the relation between theoretical and practical reason in the work of J.S. Mill. I argue that Mill holds that theoretical reason is subordinate to practical reason. Ultimately, this amounts to the claim that the norms of theoretical reason – those rules governing how we ought to believe – are grounded in considerations of utility.